Glenoid failure after total shoulder arthroplasty with cemented all-polyethylene versus metal-backed implants: a systematic review protocol. Issue 12 (24th December 2020) - Zan, Renato Aroca Aroca; Lazarini, Rafael Fuchs; Matsunaga, Fabio Teruo; Netto, Nicola Archetti; Belloti, João Carlos; Tamaoki, Marcel Jun Sugawara
Abstract : Introduction: Anatomical total shoulder arthroplasty (TSA) is an effective treatment adopted for patients with glenohumeral osteoarthritis (OA). The glenoid component failure is the main risk that occurs in this therapeutic choice; however, doubts remain regarding the selection of the best implant for avoiding complication. This systematic review aims to evaluate the glenoid component in TSA by comparing the complications of different types of implants. Methods and analysis: A systematic review of randomised clinical trials or quasi-randomised trials will be performed by applying the Preferred Reporting Items for Systematic Review and Meta-Analysis protocols and comparing polyethylene (keeled and pegged) versus metal-backed implants in adult patients with glenohumeral OA. Our search strategy will be performed using MEDLINE, PubMed, Cochrane Central Register of Controlled Trials, EMBASE and Web of Science. Data management and extraction will be performed using a data withdrawal form and by analysing study method characteristics, participant characteristics, intervention characteristics, results and methodological domains. The database search will be performed by February 2021. The Grading of Recommendations Assessment, Development and Evaluation will be used for assessing the quality of evidence of each study selected; however, some critical and important outcomes were determined such as the shoulder function through functional scores (Constant-Murley and American Shoulder and Elbow Surgeons), complications represented by pain (Visual Analogue Scale), surgical revision, radiograph radiolucency and loosening. The confidence in estimated effects for these outcomes will be applied as the overall confidence. The outcomes will be defined as early or late, according to the postoperative follow-up of less than or greater than 1 year, respectively, for complications and radiographs. For the shoulder function, follow-ups will be divided into 6, 12 and 24 months. Heterogeneity is expected in systematic reviews; therefore, the selection of outcomes, as well as the sample size, and specific statistical analysis can lead to meta-analysis; however, if it fails, narrative evidence synthesis will be conducted. Other analyses such as descriptive, subgroup and sensitivity analyses will be performed whenever possible. This systematic review will, therefore, provide evidence concerning the best clinical practice for avoiding complications. Ethics and dissemination: This study has been approved by the Institutional Review Board of Universidade Federal de São Paulo (protocols 0725/2017, 2.157.415 and 70473017.5.0000.5505), and the findings will be disseminated through peer-reviewed publication and conference presentations. PROSPERO registration number: CRD42018079537.